(untitled) (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
National Standard Madrasas Final Exam (UAMBN) is an activity of measuring and evaluating the achievement of national competency standards for graduates aimed at mapping the quality of education and measuring their achievement. The UAMBN is a form of testing that is held for all students at the end of high school. As for the cognitive level is the level of ability of students individually or in groups that can be translated into three cognitive levels (LOTS, MOTS, and HOTS). The research methodology used in this study is a mixture of qualitative and quantitative methods. Then the data collection techniques in this study were obtained through the documentation of questions UAMBN 2017/2018 school year at the level tsanawiyah. Data were analysed in qualitative and quantitative descriptive analysis (amount and percentage). Then the data were analysed descriptively by analysing in terms of cognitive level (LOTS, MOTS, and HOTS). The population in this study were all items of questions UAMBN 2017/2018 school year at the level tsanawiyah Arabic language which amounted to 40 question, and all populations were sampled for this study. The results of the cognitive level analysis research items UAMBN 2017/2018 school year at the level tsanawiyah there are 40 questions which all questions are multiple choice. In terms of quantitative questions for level LOTS found 8 questions (20%), then at level MOTS found 29 questions (72%), and at level HOTS found 3 questions (8%). As a whole the questions UAMBN Arabic language have not met the standards of good quality questions, because hey should be dominated by high level questions at this level (HOTS).